Strengthening Sustainability in the Glass Industry - World Bank; IFC (World Bank, Washington, DC, 2022)
Glass is present in a myriad of products used in both daily life and manufacturing, from beverage containers to windows to fiber optic cables. The demand for glass is projected to continue on an upward trajectory, along with growing pressure on the industry to further reduce energy use and greenhouse gas emissions. Over the last few decades, glass manufacturers have increased their sustainability through innovation, and they are expected to continue to do so through the rollout of new technologies and processes such as carbon capture. The sector also has a key role to play in boosting sustainability in other sectors, whether through lighter glass packaging or glass fiber used for wind turbine blades. All these efforts will demand further investment in research and infrastructure, from waste-management facilities to collect and recycle end-of-life glass, to a guaranteed, steady supply of carbon-free electricity, to carbon capture transport networks and storage facilities. IFC's role will be to partner with forward-thinking and innovative players to improve their energy efficiency, lower their carbon footprint, and adopt circular economy strategies.